Studi Analisis Rasi Bintang Orion Sebagai Acuan Penentu Arah Kiblat di Malam Hari Perspektif Astronomi - Sulnanda; Rahmatiah,HL; Chotban, Sippah (Universitas Islam Negeri Alauddin Makassar, 2024)
Qibla direction is the direction in which Muslims worship. The sun, stars and other celestial bodies have been used by human civilizations as clues to establish their position for several centuries, and are closely related to the implementation of worship. As an illuminator and decorator of the sky there are constellations that are used as a reference at night. Because at night the constellations can be used as directions. The constellation Orion serves as a guide for fishermen and all mankind because it is too young to be seen with the naked eye with its position pointing west. This type of research uses library research